Electrocardiographic predictors of recovery from pacemaker dependency after transcatheter aortic valve implantation: a meta-analysis. (14th October 2021) - Maier, O; Afzal, S; Piayda, K; Polzin, A; Westenfeld, R; Jung, C; Zeus, T; Kelm, M; Veulemans, V
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is a well-established alternative to surgery for the treatment of patients with severe symptomatic aortic stenosis at high and intermediate surgical risk. The occurrence of electrical conduction disturbances with the need for permanent pacemaker (PPM) implantation remains one of the most frequent complications of the procedure. But PPM dependency after TAVI is often transient and conduction abnormalities may improve over time. Purpose: We performed a meta-analysis to summarize available studies that reported the incidence of new PPM after TAVI and investigated the rate and possible predictors of recovery from PPM dependency during follow-up. Methods: The authors conducted a literature search in PubMed and MEDLINE databases from January of 2012 until February of 2021. Eleven observational studies (n=6794) met inclusion criteria for the final analysis. The effect size was estimated using a random-effects model with 95% confidence interval (CI). Results: PPM implantation was performed in 902 patients after TAVI (13.3%), mostly due to high degree atrioventricular (AV) block (81.3%). A follow-up of 683 patients was performed after a median period of 139 days. 322 of the patients examined during follow-up (48.6%) showed recovery from PPM dependency. Regarding secondary endpoints' analysis of relative risk (RR) and mean difference (MD) predictors of PPM recovery during follow-up were female sex (RR 1.37; 95% CI 1.10–1.71; p=0.006), preexisting coronary artery disease (RR 1.12; 95% CI 0.99–1.27; p=0.08) and reduced left ventricular ejection fraction (MD −2.08%; 95% CI 0.23–3.93%; p=0.03). ECG predictors for long-term PPM dependency after TAVI appeared to be preexisting right bundle branch block (RBBB) (RR 1.84; 95% CI 1.38–2.45; p<0.0001), bifascicular block (RR 4.41; 95% CI 1.64–11.86; p=0.003) and prolonged QRS duration (MD 8.69 ms; 95% CI 0.11–17.28 ms; p=0.05). While postprocedural complete heart block was highly predictive for long-term PPM dependency after TAVI (RR 1.35; 95% CI 0.97–1.89; p<0.0001), patients with recovery of PPM dependency showed more indications other than complete heart block for PPM implantation like lower degree AV block or sick sinus syndrome (RR 2.28; 95% CI 1.53–3.38; p<0.0001). Especially postprocedural AV block grade I (RR 1.73; 95% CI 0.96–3.14; p=0.07) and new left bundle branch block (LBBB) (RR 1.94; 95% CI 1.22–3.08; p=0.005) turned out to be predictors of PPM recovery during follow-up. Conclusion: This structured meta-analysis proved new PPM implantation in 13.3% of patients following TAVI with half of the cases (48.6%) recovering from PPM dependency during follow-up. Therefore, it should be considered to carefully reassess the indication for PPM rather than to immediately implant PPM after TAVI, especially regarding postprocedural ECG predictors for early pacemaker recovery (lower degree AV block, postprocedural LBBB). Funding Acknowledgement: Type of funding sources: None.